(untitled) - Allaby, Michael (Oxford, 1992)
The book offers many entries derived from the acclaimed Oxford Dictionary of Natural History; wide coverage including animal behaviour, ecology, physiology, genetics, cytology, evolution, Erath history, and zoogeography; full taxonomic coverage of anthropods, other invertebrates, fish, reptiles, amphibians, birds, and mammals
Keywords: Zoology; Dictionaries